1993
DOI: 10.1111/jon19933289
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Validation of Color Velocity Imaging and Spectral Doppler for Velocity Determination

Abstract: Color velocity imaging (CVI) is a new non-Doppler ultrasound technique for vascular color flow imaging. Using information contained in the two-dimensional B-mode, gray-scale image to determine velocity, CVI offers potential advantages over Doppler color flow imaging methods. In order to be used clinically, velocity determination with CVI must be validated by other current methods. A Doppler string phantom was studied with a Philips CVI ultrasound system. Velocity measurements were obtained by both CVI and du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…The accuracy of the flow velocity information of the color flow imaging system we used was tested in vitro [5] and in vivo [6], These data showed an excellent correla tion of actual flow velocity and indicated flow velocities as tested on a string phantom. Compared to other color duplex systems, the velocity determination on the system we used (Philips P700, Philips Ultrasound, Santa Ana, Calif., USA) is not based on the Doppler (frequencydomain) but on a time-domain principle, which deter mines flow velocities independently of the transmitted frequencies of the operating system [7], This Philips CVI (color velocity imaging) system provides a special soft ware for quantification of flow volume (CVI-Q, color velocity imaging quantify).…”
mentioning
confidence: 99%
“…The accuracy of the flow velocity information of the color flow imaging system we used was tested in vitro [5] and in vivo [6], These data showed an excellent correla tion of actual flow velocity and indicated flow velocities as tested on a string phantom. Compared to other color duplex systems, the velocity determination on the system we used (Philips P700, Philips Ultrasound, Santa Ana, Calif., USA) is not based on the Doppler (frequencydomain) but on a time-domain principle, which deter mines flow velocities independently of the transmitted frequencies of the operating system [7], This Philips CVI (color velocity imaging) system provides a special soft ware for quantification of flow volume (CVI-Q, color velocity imaging quantify).…”
mentioning
confidence: 99%
“…Phantom and human studies have shown that both CVI and SDI are accurate for assessment of flow velocity. [5][6][7][8][9] Previous studies showed that the accuracy of the constant flow measurement is within 5%. 2,8 Previously we documented that CVI is a more accurate and consistent method than SDI for determination of blood flow volume 10 ; therefore, we chose CVI as the method of investigation in this study.…”
Section: Discussionmentioning
confidence: 99%
“…The results from this study testing the centroid function on two instruments prove the accuracy of these automatic tracing devices, as compared to the string velocity. A previous study on a time domain system [ 15] showed all velocity estimates performed with a 65-degree angle as accurate representations of the actual velocity. However, under clinical circumstances some problems may be observed us- One approach to reduce the peak veloc1ty error due to intrinsic spectral broadening (ISB) is to redefine the ultrasound beam used for angle correction by the operator.…”
Section: The Cosine-dependent Correction For the Angle Of Insona-mentioning
confidence: 96%